Pengaruh Metode Demonstrasi terhadap Hasil Belajar Fisika Kelas X MA Almuhajirin Tugumulyo - Ovilia Putri Utami Gumay; Venes Bertiana (SPEJ (Science and Physic Education Journal), 2018)
The purpose of this research is to know the student learning activity on the implementation of Demonstration model. The type of this research is quantitative with experimental research method with pretest description posttest control group design or experimental control group design. The population in this study were all students of class X MA AlMuhajirin Tugumulyo, two classes were taken randomly that is class X1 as experiment class and class X2 as control class. Technique of collecting data using test technique, test score data of student analyzed by using t-test. Based on the analysis of posttest data of experimental class and control class with significant level α = 0,05 obtained tcount: 6.87 and ttable: 2.02 because t count more than t table then Ha accepted which means the average of experiment class grade is not same with class control. So it can be concluded that there is a significant influence Demonstration Method on Physics Learning Results class X Ma Al-Muhajirin Tugumulyo 2016/2017. Keywords: Demonstration Learning Model, Learning Outcomes.